Nonlinear and vector closed-loop control methods for flying-capacitor power converters. Issue 8 (3rd August 2017) - Caris, M.L.A.; Huisman, H.; Duarte, J.L.; Lomonova, E.A.
ABSTRACT: In this paper, the design and implementation of two different, nonlinear and vector, closed-loop control methods for flying-capacitor power converters are proposed and evaluated. Specific focus has been given to the decoupling problem, the influence of the balancing compensator on the output voltage reference tracking controller. In the first method, the coupling between the internal voltage balancing dynamics and the external load dynamics is solved in the pulse-width modulator by means of vector modulation. In the second method, input–output decoupling is achieved by feedback linearization to resolve the nonlinearity caused by switching the flying-capacitor voltage state. For both methods, classical linear control theory is applied in the design of a feedback control law. The theoretic evaluation is supported by simulation and experimental results.